Curators and Curatorial Practice in the Digital Arts Era - Dahlan, Nur Fadillah (Journal of Studies on Art, Culture and Society, 2024)
This study explores the evolving roles and practices of curators within the digital arts landscape. As the art world increasingly embraces digital technologies, curators must adapt their skillsets and approaches to effectively curate and present digital artworks. The research highlights the need for curators to develop new competencies, such as digital literacy, user experience design, and collaborative skills, to navigate the complexities of the digital arts domain.The findings also reveal the unique challenges faced by curators, including the preservation and conservation of ephemeral digital artworks, the integration of interactive digital technologies within exhibitions, and the disruption of the traditional curatorial gatekeeping role. Despite these challenges, the digital arts era presents curators with opportunities to enhance audience engagement, foster artistic innovation, and expand the reach of their curatorial programs through the use of digital platforms and experimental curatorial approaches.The study emphasizes the importance of curators embracing collaborative and interdisciplinary models to develop holistic strategies that leverage the synergies between digital expertise and artistic vision. As the digital arts landscape continues to evolve, this research provides insights that can inform the future of curatorial practice and the role of curators in shaping the art world of the 21st century.